Tax evasion strategies in the sale of household appliances and technology in informal commerce - Pacheco Vizcarra , Milagros Yesenia (2024)
Tax evasion through the sale of household appliances in the Túpac Amaru market in the city of Juliaca amounts to US$ 5,266,315.26, which represents income tax evasion of US$ 1,474,568.20. Likewise, the tax evasion through the sale of household appliances in the Bellavista market in the city of Puno is US$ 246,943.38. Tax evasion through the sale of technology in the Túpac Amaru market in the city of Juliaca is US$ 856,501.70, which represents income tax evasion of US$ 88,606.10. Similarly, the tax evasion through the sale of technology in the Bellavista market in the city of Puno is US$ 649,555.24, which represents income tax evasion of US$ 181,875.59. The objective was to determine the percentage of tax evasion and the methods of smuggling used. Gap: There is tax evasion and income tax evasion in these two informal markets. Analysis of tax evasion through informal trade, which hampers the economic development of a country, through the sale using various smuggling methods of household appliances and technology in the informal markets of Puno and Juliaca in Peru. Tax evasion and income tax evasion, which limits the economic development of a country. Surveys were conducted among consumers and traders, selecting a sample of 47 traders in the informal market of Bellavista Puno and 115 traders in the informal market of Túpac Amaru Juliaca.